Mother-to-infant bonding failure and intimate partner violence during pregnancy as risk factors for father-to-infant bonding failure at 1 month postpartum: an adjunct study of the Japan Environment and Children's Study. (17th August 2020) - Nishigori, Hidekazu; Obara, Taku; Nishigori, Toshie; Metoki, Hirohito; Mizuno, Satoshi; Ishikuro, Mami; Sakurai, Kasumi; Hamada, Hirotaka; Watanabe, Zen; Hoshiai, Tetsuro; Arima, Takahiro; Nakai, Kunihiko; et al.
Abstract: Objective: To survey the frequency and risk factors for father-to-infant lack of affection (LA) and anger/rejection (AR) bonding failure at 1 month postpartum. Material and methods: The study participants enrolled in the prospective birth cohort study of an adjunct study of the Japan Environment & Children's Study. Bonding failure, psychological distress during pregnancy and postnatal depression symptoms were evaluated using the Japanese version of the Mother-Infant Bonding Scale (MIBS-J), the Kessler 6-item (K6) psychological distress scale and the Edinburgh Postnatal Depression Scale (EPDS-J). This study extracted relative factors based on approximately 10% occupancy of the total high scores in MIBS-J subscales as a cut-off for bonding failure. The cut-off scores on the paternal EPDS-J were eight, on maternal EPDS-J was 9, and on the K6 psychological distress scale score was 13. Results: A total of 1008 couples who had single delivery were assessed at 1 month postpartum, respectively. The prevalence of paternal MIBS-J_LA scores ≥4 was 8.3%, MIBS-J_AR scores ≥3 was 7.9%, and EPDS-J scores ≥8 was 11.2%, respectively. In the multiple logistics analysis, paternal MIBS-J_LA scores ≥4 were significantly associated with maternal MIBS-J_LA score ≥3 (adjusted odds ratio (AOR) 2.814; 95% confidence interval (CI): 1.377–5.747), mental intimate partner violence (IPV) against the mother during pregnancy (AOR 2.176; 95% CI: 1.185–3.997), maternal K6 psychological distress scale score ≥13 (AOR 2.980; 95% CI: 1.317–6.745), paternal EPDS-J score ≥8 (AOR 3.227; 95% CI: 1.767–5.892), and a history of mental health disorder (AOR 4.125; 95% CI: 1.423–11.963). Paternal MIBS-J_AR scores ≥3 were significantly associated with maternal MIBS-J_AR scores ≥3 (AOR 5.082; 95% CI: 2.453–10.529), a history of physical IPV against the mother during pregnancy (AOR 5.230; 95% CI: 1.016–26.920), paternal K6 psychological distress scale score ≥13 (AOR 4.145; 95% CI: 1.311–13.107), and paternal EPDS-J scores ≥8 (AOR 4.479; 95% CI: 2.503–8.013). In Pearson's product moment correlation coefficient analyses between paternal and maternal MIBS-J score, MIBS-J_LA score was r = 0.2112, p < .0001, and MIBS-J_AR score was r = 0.3281, p < .0001. Conclusion: Father-to-infant lack of affection bonding failure was associated with mother-to-infant lack of affection bonding failure, mental IPV against mother during pregnancy, maternal psychological distress during pregnancy, paternal postpartum depression symptoms, and history of paternal mental health disorders. Father-to-infant anger/rejection bonding failure was associated with mother-to-infant anger/rejection bonding failure, physical IPV against mother during pregnancy, paternal psychological distress during pregnancy, and paternal postpartum depression symptoms. Since bonding failure is a risk factor for infant maltreatment, further investigations are recommended to fully assess these associations to resolve parent perinatal mental health issues for preventing father-to-infant bonding failure.